EFFECTS OF DIFFERENT SUGARS, ALCOHOLS, ANTIOXIDANTS ON GOAT MILK TABLETS CONTAINING LACTOBACILLUS ACIDOPHILUS LA-5 - DONGLIN MA; GUOWEI SHU; HE CHEN; JIANHUA ZHANG; NI XIN; JIANG PENG MENG (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Probiotics were added to goat milk powder, which would not only improve the intestinal flora balance but also would promote human and animal health. In this paper, the effects of different sugars, alcohols, antioxidants on Lactobacillus acidophilus goat milk tablets were investigated by single factor tests based on viable count, suitable hardness, friability, and sensory evaluation. The optimal formulation of goat milk tablets with Lactobacillus acidophilus was obtained: sucrose 7 %, glucose 1.3 %, xylitol 5 %, acesulfame 0.04 %, D-sodium ascorbate 0.06 %, D-mannitol 0.3 %, tea polyphenols 0.018 %, microstalline cellulose 0.4 %. The application of this composition gives good sensory evaluation, high viable lactobacilli count, suitable hardness and friability of the resulting goat milk tablets of Lactobacillus acidophilus.